Gall Bladder Visualization in Lymphoscintigraphy - Balci, Tansel Ansal; Koc, Zehra Pinar; Demirel, Bedriye Busra; Tasdemir, Bekir; Cerci, Sevim Sureyya (Mary Ann Liebert Inc, 2012)
Background: The aim of this study was to evaluate gall bladder visualization in lymphoscintigraphy of extremities. Methods and Results: Thirteen patients who had prediagnoses of lymphedema and were referred for lower extremity lymphoscintigraphy to our department were retrospectively evaluated. Lower extremity lymphoscintigraphy with Tc-99m sulfur colloid was performed on the patients, and planar images of the lower extremity and abdominal region were taken in early phase and late phase (at the 24th hour) routinely. Lymphoscintigraphy results of eight patients were normal regarding lymphatic flow or lymph nodes; however, additional pathologic tracer accumulations in gall bladder were observed, which disappeared at 24th hour images in three patients. Five patients had various pathologies regarding lymph flow or lymph nodes. However, there were no patients with gall bladder activity except those three patients who had casual anamnesis of fasting prior to the exam. Conclusion: The fasting state of the patients might be the cause of gall bladder visualization during the lymphoscintigraphy of the extremities with sulfur colloid.
Keywords: Rim Sign; Extremity Lymphedema; Scintigraphy; Cholecystitis; Gallbladder; Diagnosis; Edema; Liver